Effectiveness of Spiritual-Based Interventions in Enhancing Quality of Life Among Breast Cancer Patients: A Systematic Review - Su, Hansen Maikel; Ismail, Suhartini; Prasetyo, Awal (Media Publikasi Cendekia Indonesia, 2025)
Breast cancer is the most prevalent cancer among women and significantly affects patients' quality of life. Beyond physical symptoms, patients often experience emotional and social burdens that deteriorate their overall well-being. While medical and psychosocial interventions are widely applied, spiritual aspects are often underemphasized. Therefore, spiritual-based interventions are needed to support recovery by fostering hope, emotional stability, and a sense of life meaning.To explore the effectiveness of spiritual-based interventions in improving the quality of life of breast cancer patients. This study employed a systematic review design. Articles were retrieved from three databases CINAHL, PubMed, and Scopus using the main keywords: “breast cancer,” “quality of life,” “spiritual care,” and “spiritual intervention.” Inclusion criteria were original research articles, written in English, published between 2011 and 2025, and involving breast cancer patients. Data were extracted using structured tables and analyzed descriptively using qualitative synthesis. Seven eligible studies demonstrated that spiritual-based interventions, such as prayer, group therapy, meditation, and religious counseling, positively affect the quality of life of breast cancer patients. Key outcomes included enhanced hope, reduced pain, improved emotional, physical, and social well-being, stronger spiritual resilience, better coping mechanisms, and increased social support through group-based activities. Spiritual-based interventions significantly improve the quality of life of breast cancer patients through a holistic approach, integrating physical, emotional, social, and spiritual dimensions.